Risk factors and prognostic value of endotoxemia in patients with acute myocardial infarction - Nguyen, Maxime; Putot, Alain; Masson, David; Cottin, Yves; Gautier, Thomas; Tribouillard, Laura; Rérole, Anne-Laure; Guinot, Pierre-Grégoire; Maza, Maud; Pais de Barros, Jean-Paul; Deckert, Valérie; Farnier, Michel; et al. (Frontiers in Cardiovascular Medicine, 2024)
BACKGROUND: There is increasing evidence regarding the association between endotoxemia and the pathogenesis of atherosclerosis and myocardial infarction (MI). During the acute phase of MI, endotoxemia might enhance inflammation and drive adverse cardiovascular (CV) outcomes. We aimed to explore the risk factors and prognostic value of endotoxemia in patients admitted for acute MI.METHODS: Patients admitted to the coronary care unit of Dijon University Hospital for type 1 acute MI were included between 2013 and 2015. Endotoxemia, assessed by plasma lipopolysaccharide (LPS) concentration, was measured by mass spectrometry. Major adverse CV events (MACE) were recorded in the year following hospital admission. RESULTS: Data from 245 consecutive MI patients were analyzed. LPS concentration at admission markedly increased with age and diabetes. High LPS concentration was correlated with metabolic biomarkers (glycaemia, triglyceride and total cholesterol) but not with CV (troponin Ic peak, Nt pro BNP) or inflammatory biomarkers (C-reactive protein, IL6, IL8, TNFα). LPS concentration was not associated with in-hospital or one-year outcomes.CONCLUSIONS: In patients admitted for MI, higher levels of endotoxins were related to preexisting conditions rather than acute clinical severity. Therefore, endotoxins measured on the day of MI could reflect metabolic chronic endotoxemia rather than MI-related acute gut translocation.